Histopathological changes and tumour necrosis factor-alpha, transforming growth factor-beta and tenascin expression in patients with primary type I membranoproliferative glomerulonephritis in remission - ARIKAN, İZZET HAKKI; KOÇ, MEHMET; TUĞLULAR, ZÜBEYDE SERHAN (WILEY, 2009)
Aim: Primary type I membranoproliferative glomerulonephritis (MPGN) is a rare cause of glomerular disease with a high relapse rate and poor prognosis. The aim of this study was: (i) to evaluate the histopathological findings associated with remission; and (ii) to document the possible clinical and histopathological factors predicting relapses. Methods: Eleven type I MPGN patients (five men, six women; mean age, 38.8 +/-13.5 years) who were in remission for at least 1 year after the cessation of immunosuppressive drugs were re-biopsied. The intensity of immunostaining for tumor necrosis factor (TNF)-alpha, transforming growth factor (TGF)-beta 1, and tenascin was graded from 0 (no staining) to 3+ (maximum staining). Results: Mean baseline mesangial cellularity score and tubulointerstitial infiltration score were reduced and mesangial matrix expansion score was increased at protocol re-biopsies compared to baseline. The glomerular and tubulointerstitial staining scores for TGF-beta 1 and tenascin were higher than that of baseline. Reduced tubulointerstitial TNF-alpha expression was found in re-biopsy specimens compared to baseline. Patients have been followed for a mean time of 51.5 +/- 22.2 months after the protocol biopsy. Eight patients had a relapse. Mesangial cellularity score and glomerular tenascin expression at re-biopsy specimens were higher in relapsed patients compared to those without a relapse. Conclusion: Our study shows that mesangial cellularity and tubulointerstitial cell infiltration are reducing whereas mesangial matrix expansion, glomerular and tubulointerstitial TGF-beta 1 and tenascin expression are increasing with remission. The higher mesangial cell proliferation and glomerular tenascin scores in remission are associated with the development of relapse.
Keywords: histopathology; primary membranoproliferative glomerulonephritis; re-biopsy; relapse; tenascin; RAT MESANGIAL CELLS; EXTRACELLULAR-MATRIX; PATHOLOGICAL CONDITIONS; EPITHELIAL-CELLS; IGA NEPHROPATHY; TNF-ALPHA; THERAPY; PROLIFERATION; CHILDREN